Integrating Virtual Reality in Occupational Therapy Education - Lassen, Anna Marie; Kaptain, Rina Juel (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
In the early semesters of the occupational therapy education, students often struggle to develop a deeper un-derstanding of clinical practice, their professional responsibilities, and the challenges faced by future clients. Vir-tual reality (VR) offers the potential to immerse students in specific situations, such as everyday life scenarios or health-related experiences, thereby enhancing their understanding. This study builds on the theoretical founda-tion that VR can support reflection and subsequent action, contributing to practice-based learning. The teaching was guided by the Reflective Practice-Based Learning (RPL) principle 4: ‘The Good Example’, in which students share a common experience that serves as a basis for collective reflection. The study aimed to explore the ex-periences of both students and educators when integrating VR into occupational therapy education. Two types of data were collected: 1) Evaluation data – four VR sessions were conducted during relevant teaching activi-ties, followed by short questionnaires addressing the experiences of both students and educators; 2) Workshop data – students tested VR and brainstormed possible applications in education. The TPACK model, along with the analytic elements from RPL Experience, Thinking, and Action, was used to support the analysis. Findings indicate that VR provides a safe and realistic environment in which students can observe and experience clini-cally relevant scenarios. It enhances empathy, deepens understanding of client challenges, and helps bridge the gap between theory and practice. Overall, based on the students’ expressed interests and suggestions, there is clear potential for further development and exploration of VR in occupational therapy education.